RIZWAN KHAN’S STRUGGLES AGAINST NEGATIVE STEREOTYPES LABELED TO MOSLEM AMERICANS IN MY NAME IS KHAN MOVIE - PRISMADIANTO, GITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: stereotypes, terrorist, exclusivity, radicalism, Moslems American.Humans are social beings and groups who are capable to live in harmony. However it is possible that different group of people will have a different assessment to the other groups, it can be positive and negative. The writer conducts a study of stereotypes in the movie entitled My Name Is Khan . The movie shows the phenomena occurring in America after the tragedy of 9/11. There is a problem that will be answered in this study, namely Khan’s struggle against negative stereotypes labeled to Moslem Americans in My Name is Khan Movie. This study uses the theory of stereotypes to analyze the data for discovering the kinds of stereotype suffered by Moslems in America.The results of the study shows that there are three struggles made by the main character, Khan, to fight against negative stereotypes, (1) In the fight against this stereotype, Khan tries to explain to everyone that his name is Khan and he is not a terrorist, (2) Khan tries to tell a group of people at the mosque that think Moslems are not radical, but a peaceful religion, (3) Khan tries to help others regardless of differences in race, religion and color of skin, so the assumption of most Americans who think that Moslems are difficult to mingle with other people is not true.In conclusion all the assumptions and negative stereotypes directed towards Moslem is not true and it can be proved by the struggles made by Khan to fight against negative stereotypes labeled to Moslem Americans. Thus, the writer suggests to another researcher to conduct further research Discrimination by using discrimination theories to analyze this movie, for example by using discrimination theory to reveal whether there is a discrimination to create bad image towards moslems in America.